Peningkatan Literasi Ekonomi Syariah bagi Ibu-Ibu PKK di Kelurahan Rimba Sekampung, Kabupaten Bengkalis: Penelitian - Annisa Fitri; Nadrah; Faisal; Khodijah Ishak; Zul hendri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to improve Islamic economic literacy among PKK mothers in Rimba Sekampung Village, Bengkalis Regency through training and seminars covering the introduction to Islamic economics, utilization of rhizomes as sources of income and health, and family financial management based on Islamic principles. The method used was an educative-participatory approach involving interactive lectures, group discussions, herbal product making practices, as well as pre-tests and post-tests to measure participants’ understanding improvement. A total of 30 PKK mothers actively participated in the activities. The results showed significant improvement in understanding Islamic economics, skills in processing rhizomes into marketable products, and the ability to manage family finances according to Islamic principles. The average pre-test score of 42% increased to 81% in the post-test. Evaluation also indicated a 90% satisfaction rate, with participants stating that the training was beneficial and opened opportunities for economic independence. Thus, the training and seminar effectively increased Islamic economic literacy and empowered local community economies. It is recommended that similar activities be conducted sustainably.